Knowledge-Based Software Engineering: 2018 Proceedings of the 12th Joint Conference on Knowledge-Based Software Engineering (JCKBSE 2018) Corfu, Greece - Virvou, Maria; Kumeno, Fumihiro; Oikonomou, Konstantinos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book summarizes the new research results presented at the 12th Joint Conference on Knowledge-Based Software Engineering (JCKBSE 2018), which took place on August 27-30, 2018 on the island of Corfu, Greece. The JCKBSE is a well-established international biennial conference that focuses on the applications of Artificial Intelligence in Software Engineering. The JCKBSE 2018 was organized by the Department of Informatics of the University of Piraeus, the Department of Computer and Information Engineering of Nippon Institute of Technology, and the Department of Informatics of Ionian University. The book will benefit not only experts and researchers in the field of (Knowledge-Based) Software Engineering, but also general readers in the fields of Artificial Intelligence, Computational Intelligence and Computer Science who wish to learn more about the field of (Knowledge-Based) Software Engineering and its applications. An extensive list of bibliographic references at the end ofeach paper encourages readers to probe further into the application areas that interest them most.
Ripple Effect Analysis Method of Data Flow Diagrams in Modifying Data Flow Requirements -- Analysis of Speciﬁcation in Japanese using Natural Language Processing -- Deriving Successful Factors for Practical AI System Development Projects using Assurance Case -- Estimation of business rules using Associations analysis -- A Fast Learning Recommender Estimating Preferred Ranges of Features -- Quantitative Evaluation of IT Management Activity Knowledge -- A Knowledge Transfer Support System from Text-based Work Reports with Domain Ontologies -- Group affect Recognition: Optimization of Automatic Classiﬁcation -- An Artiﬁcial Immune System-Based Approach for the Extraction of Learning Style Stereotypes -- A Sightseeing Guidebook Automatic Generation Printing System According to the Attribute of Tourist (KadaTabi) -- The Development of the System which Creates Lecture Contents by a Combination of Various Units and Learning Contents.
Keywords: Computational intelligence; Artificial intelligence; Software engineering; Computational Intelligence; Artificial Intelligence; Software Engineering